2017
DOI: 10.1038/srep44480
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities of aquatic environments on Heard Island characterized by pyrotag sequencing and environmental data

Abstract: Heard Island in the Southern Ocean is a biological hotspot that is suffering the effects of climate change. Significant glacier retreat has generated proglacial lagoons, some of which are open to the ocean. We used pyrotag sequencing of SSU rRNA genes and environmental data to characterize microorganisms from two pools adjacent to animal breeding areas, two glacial lagoons and Atlas Cove (marine site). The more abundant taxa included Actinobacteria, Bacteroidetes and Proteobacteria, ciliates and picoflagellate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 88 publications
(122 reference statements)
1
6
0
Order By: Relevance
“…Proteobacteria demonstrated the highest levels in the BFT1, BFT2 and RAS, whereas Firmicutes was the dominant phylum in WE treatment. In accordance with the present results, previous studies revealed that Proteobacteria is the dominant phylum in outdoor ponds supplied with different feeds (Qin et al., 2016), in BFT systems supplied with different carbon sources (Deng et al., 2018), the main bacteria for treatment waste water in biofloc system (Paniagua‐Michel, 2017; Quijano, Arcila, & Buitrón, 2017) and even in natural aquatic environments (Allen & Cavicchioli, 2017). Proteobacteria were dominant in commercial scale recirculating and semi‐closed aquaculture systems (Rud et al., 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Proteobacteria demonstrated the highest levels in the BFT1, BFT2 and RAS, whereas Firmicutes was the dominant phylum in WE treatment. In accordance with the present results, previous studies revealed that Proteobacteria is the dominant phylum in outdoor ponds supplied with different feeds (Qin et al., 2016), in BFT systems supplied with different carbon sources (Deng et al., 2018), the main bacteria for treatment waste water in biofloc system (Paniagua‐Michel, 2017; Quijano, Arcila, & Buitrón, 2017) and even in natural aquatic environments (Allen & Cavicchioli, 2017). Proteobacteria were dominant in commercial scale recirculating and semi‐closed aquaculture systems (Rud et al., 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Universal primer pairs (926wF: 5′-AAACTYAAAKGAATTGRCGG-3′ and 1392R: 5′-ACGGGCGGTGTGTRC-3′) targeting the V6-V8 hyper-variable region of the 16S/18S ribosomal RNA gene with an Illumina-specific overhang were used 26 . These primers have been tested previously in silico against the Silva database and shown to amplify 84%, 71% and 91% of rRNA gene sequences from Bacteria, Archaea and Eukaryota, respectively 27 . For each sample, triplicate PCR reactions obtained with 22 cycles were pooled and purified using Agencourt AMpure XP beads (Beckman Coulter, Singapore).…”
Section: Methodsmentioning
confidence: 99%
“…Of each sample, PCR was done in triplicates using KAPA HiFi HotStart ReadyMix (Roche, Cape Town, South Africa) with primers that have the standard Nextera Illumina adapter attached at their 5’ end. The primer pair, 926WF (5’-AAA-CTY-AAA-KGA-ATT-GRC-GG-3’) and 1392R (5’-ACG-GGC-GGT-GTG-TRC-3’) 19 was used specifically because it targets the V6-V8 hypervariable region of the SSU rRNA gene of all three bacteria, archaea, and eukarya at a considerably high coverage for environmental samples 20, 21 . After 22 cycles of amplification, triplicate amplicons of the same samples were pooled and then cleaned using KAPA HyperPure Beads (Roche).…”
Section: Methodsmentioning
confidence: 99%